The Effects of Natural Disasters on Development: A Case of Uganda - Barbara, Alungat (Journal of Public Policy and Administration, 2022)
Purpose: To examine the effects of natural disasters on development in Uganda. Methodology: The study adopted documentary review as a data collection technique in which data is gathered from reports from different sources, journals, magazines, newspapers, institutional archives, reports and articles which have data linked to the research being undertaken (Creswell, 2014). A documentary review checklist was employed to solicit data related to an examination of effects of natural disasters on development in Uganda from the Ministry of Disaster Preparedness and Refugees archives. This method was preferred by the researcher over other methods because was able to gain permission to access information from different department at the Ministry of Disaster and preparedness archives. In addition, using document analysis takes out the personal aspect of the effect a researcher might have on an individual during an interview. Findings: Epidemics have been the most important public health emergency in the districts of Uganda and neighboring countries. The situation has been worsened by the outbreak of COVID-19 being first reported in Wuhan, China in December 2019 (WHO, 2019). The most threatening epidemics in Uganda include Ebola, Marburg, Cholera HIV/AIDS and Malaria but the discussion on epidemics here will be limited to Ebola, Malaria and crop and animal diseases (Mullen et al, 2020). Floods and landslides are another type of natural disasters that affect development in Uganda leaving direct destruction or impacts on assets (Botzen et al, 2019). In addition, famine is the most dominant natural disasters Uganda faces from time to time despite having the necessary conditions for food security like fertile land and a favorable climate for agriculture as a large part of the population across the country fall victim to famine regularly (Government of Uganda, 2010). Disasters continue disrupting lives, livelihood and leaving adverse effects on individuals, communities, economies and even governments and ultimately affecting development. Unique Contribution to Theory, Practice and Policy: It's therefore recommended that disaster management should focus on mitigation against identifiable Threats. The disaster management should also create more robust systems that can withstand a variety of known and unknown shocks. The disaster management theory may be used to anchor future studies in the disaster management sector